Lipid Peroxidation and Antioxidant Status in Preeclampsia - S.V. Kashinakunti; Sunitha H; K. Gurupadappa; D.S. Shankarprasad; G.Suryaprakash; J.B Ingin (Al Ameen Medical College, 2010)
The current theory suggests that in preeclampsia there is an increase in the lipid peroxidation products and leads to decrease in the serum antioxidants except uric acid, contributing to the pathogenesis of preeclampsia. In this context, this study was undertaken to determine the changes in blood levels of lipid peroxide and antioxidant levels in women with preeclampsia.Method: Case control study consisting of 30 preeclamptic and 30 healthy pregnant women. Fasting venous blood samples were collected during antepartum period and serum levels of malondialdehyde, ascorbic acid (Vitamin C) and uric acid were measured. In the preeclamptic group malondialdehyde (MDA), a lipid peroxidation product was significantly increased, while serum antioxidant ascorbic acid was significantly decreased (P< 0.001), where as uric acid level increased significantly (P<0.001). The findings of the present study are consistent with previous studies, suggesting that lipid peroxidation is an important factor in the pathogenesis of preeclampsia. In preeclampsia serum antioxidants are excessively utilized to counteract the cellular changes mediated by free radicals